Greek Medicine From Hippocrates to Galen Selected Papers - Jouanna, Jacques (Brill, 2012)
This volume makes available in English translation a selection of Jacques Jouanna's papers on Greek and Roman medicine, ranging from the early beginnings of Greek medicine to late antiquity.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Medical / History; Medicine; Electronic books